Maternal Benzophenone Exposure Impairs Hippocampus Development and Cognitive Function in Mouse Offspring (Adv. Sci. 23/2021). Issue 23 (8th December 2021) - Cui, Fengzhen; Pan, Qingfei; Wang, Siyi; Zhao, Faming; Wang, Runxin; Zhang, Tingting; Song, Yaying; He, Jun; Zhang, Haolin; Weng, Qiang; Jin, Yang; Xia, Wei; et al.
Abstract : Maternal Benzophenone Exposure In article number 2102686 by Shunqing Xu, Yaohui Tang, Xia Sheng, and co‐workers, it is reported that maternal exposure to benzophenone and its major metabolite 4‐hydroxybenzophenone during pregnancy causes endoplasmic reticulum proteotoxicity and neuroinflammation, which lead to cognitive dysfunction and neurodevelopmental toxicity in offspring mice. This alerts that the excessive use of personal care products during pregnancy may impair child's neurodevelopment.